Left atrial minimum volume and reservoir function as correlates of left ventricular diastolic function: impact of left ventricular systolic function. Issue 10 (29th April 2012) - Russo, Cesare; Jin, Zhezhen; Homma, Shunichi; Rundek, Tatjana; Elkind, Mitchell S V; Sacco, Ralph L; Di Tullio, Marco R
Abstract : Objective: Left atrial (LA) maximum volume (LAVmax ) is an indicator of left ventricular (LV) diastolic function. However, LAVmax is also influenced by systolic events, whereas the LA minimum volume (LAVmin ) is directly exposed to LV pressure. The authors hypothesised that LAVmin may be a better correlate of LV diastolic function than LAVmax . Design: Cross-sectional. Setting: University hospital. Patients: 357 participants from a community-based cohort study. Methods: LA volumes and reservoir function, measured as total LA emptying volume (LAEV) and LA emptying fraction (LAEF), were assessed by real-time three-dimensional echocardiography. LV diastolic function was assessed by trans-mitral early (E) and late (A) Doppler velocities and mitral early diastolic velocity by tissue-Doppler (e'). LV systolic function was assessed by LV ejection fraction (LVEF) and global longitudinal strain (GLS) by speckle-tracking. Results: LAVmin significantly increased with worsening diastolic dysfunction (p<0.001), whereas the increase in LAVmax was less pronounced (p=0.07). LAEV and LAEF decreased with worsening diastolic dysfunction (both p<0.001). In linear regressions, LAVmin and LAVmax were significant predictors of E/e', with higher parameter estimates for LAVmin . In multivariate models, LAVmin resulted strongly associated with E/e' (β=0.45, p<0.001), whereas LAVmax was not (β=−0.16, p=0.08). LA reservoir function was better associated with GLS than LVEF. In multivariate analyses, GLS was significantly associated with LAVmax (β=−0.15, p=0.002), LAEV (β=−0.37, p<0.001) and LAEF (β=−0.28, p<0.001) but not with LAVmin . Conclusions: LAVmin is a better correlate of LV diastolic function than LAVmax . The impact of LV longitudinal systolic function on LA reservoir function might explain the weaker relation between LAVmax and LV diastolic function.